Differences and characteristic femorl bone of todays leaving red deer and red deer from Vučedol cultural period (3 500 year BC.) - Mihelić, Damir (Array, 1996)
Research was carried out at 3120 bones fragments discovered on Vučedol area in period 1981 to 1984 year. Bone fragments was determined as part of deer"s femoral bone (6 of them). Trochlea patellae in "Vučedol deer" was remarcably bigger, but wider and in distall part some shallow then trochlea in todays leaving red deer. The distal part of trochlea patellae almost continually cross in to cranial surface of femoral condyl but without intensive protruding in dorsocaudal direction. Beside boundary-line of laterally condyl and lateral border of trochlea, in both deer group, niche for accepting ligament was espled. In Vučedol deer that niche was more wide and deeper. Fossa poplitea is more wider and deeper but obviously shorter than fossa in todays leaving red deer. We explane that the labia laterales finished in different manner considering the deer group. Based on mentioned characteristic and largenes of femoral bone, we preferred that the found bone fragments really belong to the red deer. That red deer was remarcable bigger than today leaving red deer in the Baranja diatrict respectively Vučedol area.